2017
DOI: 10.1080/02640414.2016.1273539
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of the alternative maximal accumulated oxygen deficit method to discriminate training status

Abstract: The purpose of the study was to investigate the sensitivity of an alternative maximal accumulated oxygen deficit (MAOD) method to discriminate the "anaerobic" capacity while comparing: least trained (LT) participants (n = 12), moderately trained (MT) participants (n = 12), endurance trained (ET) participants (n = 16), and rugby (RG) players (n = 11). Participants underwent a graded exercise test on a treadmill and a supramaximal effort for assessing MAOD. MAOD was calculated as the sum of oxygen equivalents fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 27 publications
5
37
1
Order By: Relevance
“…A possible explanation could be related to the differences between the two methods of determination of the anaerobic metabolism. The MAOD ALT is based on the sum of the oxygen equivalents corresponding to glycolytic and phosphagen pathways estimated during the supramaximal effort 5 8 19 20 . The latter takes into account an energetic equivalent expressed relative to the individual’s body mass (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation could be related to the differences between the two methods of determination of the anaerobic metabolism. The MAOD ALT is based on the sum of the oxygen equivalents corresponding to glycolytic and phosphagen pathways estimated during the supramaximal effort 5 8 19 20 . The latter takes into account an energetic equivalent expressed relative to the individual’s body mass (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The MAOD ALT seems to be an advantageous tool for use during routine training because it allows the estimation of anaerobic capacity in only one supramaximal exercise session. Furthermore, the MAOD ALT allows discrimination of the glycolytic and phosphagen metabolisms, enabling analysis of the specific responses in each metabolism 23 and it can be considered a sensitive enough procedure to distinguish the “anaerobic” capacity in individuals with different training levels 19 . Regarding the reliability, although the points obtained from the differences between MAOD ALT values are distributed around the systematic error, there was a limit of agreement in test-retest corresponding to ±0.54L ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To eliminate any influence of circadian variation, each subject completed all trials at the same time period of day in controlled environmental conditions regarding temperature (22.9 ± 1.3°C) and relative humidity (43.8 ± 6.3%). In all efforts, participants were verbally encouraged to perform maximally and wore a chest harness with the rope attached to the ceiling to ensure maximal effort without fall risk (except the 30-s ATR) [ 13 , 15 ]. Prior to each exercise trial, the subjects responded to the profile of mood states scale to measure their motivation for the effort.…”
Section: Methodsmentioning
confidence: 99%
“…Recently Zagatto et al [ 13 ] reported the validity, reliability and reproducibility of the MAOD ALT for estimating the anaerobic capacity in treadmill running, evidencing that exercise intensity at 115% of maximal oxygen uptake (iVO 2max ) is the greatest intensity for MAOD ALT determination. In addition, this same group of authors recently reported that MAOD ALT assessed in treadmill running can be considered a sensitive enough procedure to distinguish the anaerobic capacity in individuals with different training levels (untrained, moderately active, recreational endurance runners and elite rugby sevens players) [ 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…The AC [La−]+EPOCfast is an advantageous method for anaerobic capacity assessment and its validity has been demonstrated by the absence of significant differences with the conventional MAOD determined in cycling ( 6 , 7 ), running ( 8 ), and table tennis ( 12 , 13 ). Furthermore, AC [La−]+EPOCfast method has shown high reliability (intraclass correlation coefficient [ICC] = 0.87 and typical error = 0.27 L) and significant associations with mechanical variables assessed in a 30 s maximal effort ( 14 ), besides to be sensitive in distinguishing individuals with different physical conditioning status ( 15 ).…”
Section: Introductionmentioning
confidence: 99%